Compliance with the 24-Hour movement guidelines for the early years: Cross-sectional and longitudinal associations with executive function and psychosocial health in preschool children. Issue 9 (September 2020) - McNeill, Jade; Howard, Steven J.; Vella, Stewart A.; Cliff, Dylan P.
Abstract: Objective: To examine whether meeting the Australian 24-Hour Movement Guidelines was associated with cognitive and psychosocial health in preschoolers. Design: Prospective observational study. Methods: Cross-sectional (n = 247) and 12-month longitudinal (n = 185) data from the PATH-ABC study were examined. Physical activity was assessed by accelerometry. Parents reported children's screen time and sleep. Children were categorised at baseline as meeting: i) none/one guideline, ii) two guidelines, or iii) 24-Hour Movement Guidelines. Associations with executive functions and psychosocial health were examined using linear regression, adjusting for covariates and preschool clustering. Longitudinal associations were additionally adjusted for baseline levels of development. Results: High proportions of children met the physical activity (94.3%) and sleep (89.9%) guidelines, 17.8% and 17.4% met screen time and 24-Hour Movement Guidelines, respectively. Cross-sectionally, children meeting both sleep and physical activity guidelines displayed better phonological working memory ( p = 0.026) and shifting ( p = 0.034) scores compared to children who did not. Meeting two ( p = 0.037) and three ( p = 0.017) guidelines were associated with better phonological working memory and shifting scores, respectively (vs. meeting 0/1 guideline). Longitudinally, children meeting the physical activity guideline at baseline displayed better shifting performance 12-months later compared to those who did not ( p < 0.002). No associations with remaining cognitive outcomes, and no associations with psychosocial outcomes were evident. Conclusions: Null associations suggest that meeting the recommendations may not be adequate for broad cognitive and psychosocial health outcomes in preschoolers. However, supporting preschool children to meet the physical activity and sleep guidelines, may be beneficial for aspects of cognitive health.